Collaborative Character, Cognitive Psychology, and Process Skills: The Impact of Character-Based Mathematics Learning in High Grades of Elementary Schools - Kamid; Ramalisa, Yelli; Fajriah, Noor; Kurniawan, Dwi Agus; Perdana, Rahmat; Rivani, Putri Ayu; Widodo, Rido Ilham; Ningsih, Irma Widya (Journal of Education Reseach and Evaluation, 2023)
Learning mathematics is preparing students to be able to use a mathematical mindset in their daily lives. Learning mathematics helps children get used to doing analysis and finding the best solution to a problem. This study analyze how the effect of mathematical process skills, cognitive psychology on the collaboration abilities of fifth grade elementary school students in learning mathematics in geometry material. The research was conducted using mixed research methods and sequential explanatory research. Mixed method research relies on two types of data, namely quantitative data and qualitative data to solve a problem at hand. Fifth grade students were used as research subjects, and 18 students were selected from each school, so that the results obtained were not biased, the data collection technique used simple random sampling. This study uses two types of tests, namely the assumption test and hypothesis test, using the homogeneity test, linearity test, and normality test in the assumption test, as well as the t test and regression test in hypothesis testing. The results showed that there was a significant positive effect between the fifth grade students' mathematical process skills variables and the collaboration character.